2006
DOI: 10.1109/acsac.2006.46
|View full text |Cite
|
Sign up to set email alerts
|

Secure Distributed Cluster Formation in Wireless Sensor Networks

Abstract: In wireless sensor networks, clustering sensor nodes into small groups is an effective technique to achieve scalability, self-organization, power saving, channel access, routing, etc. A number of cluster formation protocols have been proposed recently. However, most existing protocols assume benign environments, and are vulnerable to attacks from malicious nodes. In this paper, we propose a secure distributed cluster formation protocol to organize sensor networks into mutually disjoint cliques. Our protocol ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
86
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 25 publications
(42 reference statements)
0
86
1
Order By: Relevance
“…This section briefly reviews existing approaches that are developed for sensor clustering in hostile situations [1], [2], [3], [7], [4], [5], [6]. We found that these protocols either ignore or do not effectively solve the security of leader election.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…This section briefly reviews existing approaches that are developed for sensor clustering in hostile situations [1], [2], [3], [7], [4], [5], [6]. We found that these protocols either ignore or do not effectively solve the security of leader election.…”
Section: Related Workmentioning
confidence: 99%
“…The techniques in [1], [2] focus on the security issues during the formation of initial clusters. They do not consider the security of cluster leader election.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Algorithms for the full (k,r)-clustering problem is presented in [7] and [9], but neither is self-stabilizing. The algorithm presented in [8] groups nodes together without assigning cluster heads. It considers malicious nodes inside the network, but is not self-stabilizing.…”
Section: Introductionmentioning
confidence: 99%